2017
DOI: 10.1007/s10508-016-0898-9
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Discourses of Shame, Secrecy, and Silence: Migrant and Refugee Women’s Experiences of Sexual Embodiment

Abstract: In Australia and Canada, the sexual health needs of migrant and refugee women have been of increasing concern, because of their underutilization of sexual health services and higher rate of sexual health problems. Previous research on migrant women’s sexual health has focused on their higher risk of difficulties, or barriers to service use, rather than their construction or understanding of sexuality and sexual health, which may influence service use and outcomes. Further, few studies of migrant and refugee wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 91 publications
9
89
0
2
Order By: Relevance
“…Such studies have found that many cultural groups continue to experience unmet reproductive health needs post-resettlement, including low rates of contraceptive uptake, and increased risk of unintended pregnancy Ngum Chi Watts, Liamputtong, and Carolan 2014). These issues have, in part, been attributed to inadequate contraceptive knowledge , concerns about the health risks of hormone-based contraception (Hawkey, Ussher, and Perz 2018;Rogers and Earnest 2014), religious beliefs (Ellawela et al 2017;Srikanthan and Reid 2008), and cultural norms that impede discussions of sexual and reproductive health (Rogers and Earnest 2014;Ussher et al 2017). Furthermore, several studies have described how, at times, male partners' decision-making authority overrides women's preferences to use contraception (Dengi, Koivusilta, and Ojanlatva 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have found that many cultural groups continue to experience unmet reproductive health needs post-resettlement, including low rates of contraceptive uptake, and increased risk of unintended pregnancy Ngum Chi Watts, Liamputtong, and Carolan 2014). These issues have, in part, been attributed to inadequate contraceptive knowledge , concerns about the health risks of hormone-based contraception (Hawkey, Ussher, and Perz 2018;Rogers and Earnest 2014), religious beliefs (Ellawela et al 2017;Srikanthan and Reid 2008), and cultural norms that impede discussions of sexual and reproductive health (Rogers and Earnest 2014;Ussher et al 2017). Furthermore, several studies have described how, at times, male partners' decision-making authority overrides women's preferences to use contraception (Dengi, Koivusilta, and Ojanlatva 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Young women who had received sexuality education through schools, parents or other family members were less likely to engage in risky sexual behaviors in previous studies (41,42 according to the study conducted in Northwest Ethiopia (21).…”
Section: Discussionmentioning
confidence: 75%
“…In many non-Western cultures, participation in the experimental sex research that Chivers’ reviews would be considered culturally unacceptable, with women not expected to know or talk about sex, and certainly not to view or respond to visual images of naked or copulating couples, or to exhibit same-gender desire or response (Ussher et al, 2017). In contrast, in Western societies, the proliferation of “raunch culture” is associated with increased acknowledgment of women’s agentic sexuality (Bale, 2011), including the visibility of “girl-on-girl” sex, in television shows, movies, and “girls gone wild” videos (Levy, 2005; Thompson, 2006).…”
Section: Explaining the “Mystery” Of Heterosexual Women’s Gender-nonsmentioning
confidence: 99%